THE TRADING-CRAFT CLASS, THE CHURCH AND THE PECULIARITIES OF FEUDALISM IN EASTERN GEORGIA IN THE XVI-XVIII CENTURIES - Маргарян, Гор Араратович (History, Archeology and Ethnography of the Caucasus, 2022)
Since the Early Middle Ages, it had been characteristic for the countries with feudal social system that not only the great secular rulers, but also the cleric power acted as major feudalists. This refers to the Georgian reality as well, where the Georgian Church was especially developed, and acted as one of the major feudal lords in the Late Middle Ages. The Georgian Church, represented by the Catholicosate of Mtskheta, possessed a large number of various immovable property (villages, lands, gardens, oil mills, etc.), and at the same time acted as a major serf owner. The Georgian Church enjoyed the favor and support of the Georgian royal houses and sometimes foreign rulers, such as the Safavid shahs, which was often expressed by giving donations to the church, or more importantly, by granting the church a partial or full tax exemption. The latter circumstance was especially important for the church serfs: as a result, they gained tax reliefs and a privileged status. This was very important giving the fact that in the 16th-18th centuries, Georgia, like Armenia, was divided into eastern and western parts, between Iran and the Ottoman Empire respectively, and of course, the heavy tax burden of the foreign domination would hinder the development of trade and crafts. In light of this, the tax benefits and a relatively privileged status that could be obtained by becoming a church serf would have been a desirable condition for merchants and craftsmen. The purpose of this article is to examine the question of whether the Georgian Church could be observed as a powerful aegis and a desirable patron by the trading-craft class, whether the church, in that case, would have shown some interest in replenishing the ranks of serfs with merchants and craftsmen, what ethnicity could those serfs be and other related matters.
Keywords: Georgia; Georgian Church; feudalism; serfs; privileged status; trading-craft class; trade.